Georgia : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1997)
This paper reviews economic developments in Georgia during 1990-96. Following the implementation of tight financial policies and the liberalization of prices, trade, and the exchange system, growth resumed in 1995 and accelerated in 1996, against the background of a stable exchange rate and declining inflation. At the same time structural reform continued to advance, laying the ground for increased private sector activity and sustained growth in the medium term. Following the introduction of the lari in October 1995, a gradual remonetization of the economy took place, and gross international reserves were replenished.